O déficit de memória em ratos privados de sono é prevenido pela interação dos componentes homeostático e circadiano - Rolim, Sérgio Arthuro Mota [UNIFESP] (2007)
Several studies have shown that sleep deprivation (SD) produces deficits in the performance of hippocampus-dependent learning tasks, as inhibitory avoidance (IA). However, the mechanisms underlying these effects are not completely understood. In this study, we investigated the relationship of the homeostatic (increasing in sleep duration after sleep deprivation) and circadian mechanisms (tendency to start sleep in periods around 24 hours) in memory deficits induced by SD. To do this, male Wistar rats were trained in the IA task in four different times of the day (08:00h, 14:00h, 20:00h or 02:00h) with the purpose to verify if the performance of rats in this task depends on the time of the day (experiment 1). In another experiment, the animals were sleep-deprived for 96 hours using the modified multiple platform method. SD procedure started and finished in four different times of the day: 08:00h, 14:00h, 20:00h, or 02:00h. Immediately after SD, animals were then trained in an IA task (experiment 2), or allowed to sleep 12 hours (sleep window, SW) before IA training (experiment 3). In this third experiment, SW happened predominantly during light phase or dark phase, or divided between them. Two test sessions in this task were performed: 1 hour (test 1) and 24 hours (test 2) after training session. The results of experiment 1 showed that rat’s performance in IA was not different in the four times of the day tested. In experiment 2, sleep-deprived rats showed significant impairment in IA performance, when compared to control group, in all four times of the day tested. In experiment 3, only the sleepdeprived rats that had SW during light phase (which is also the resting phase of these animals) did not show significant impairment in IA performance when compared to control group. With the purpose to investigate sleep architecture during the 12 hours of SW, we realized polysomnographic recordings when SW happens predominantly during light or dark phases (experiment 4). In this last experiment, we found an increasing in paradoxical sleep when we compare the 12 hours of SW (such in light phase as in dark phase) with basal (before SD) condition. However, when we compare sleep parameters of SW in the light phase with SW in the dark phase, we found a greater sleep efficiency and a fewer number of awakenings in SW during light phase. This result suggests that the circadian mechanism is still acting during SW, because it is different according to the circadian phase it happens. Our results also indicate that the coincidence between homeostatic and circadian mechanisms (SW during resting phase) allowed a more robust and organized sleep rebound, which could influence positively learning and memory of sleep-deprived rats.